The Effect of Education on Parents' "Speak Up" Knowledge Regarding Patients Safety in Hospital - Septy Nur Aini; Sri Mulatsih; Patricia Suti Lasmani (Jurnal Ners, 2017)
Introduction: Safety is a global issue in hospitals. Unexpected events or errors related to health services occur in children, and about 75% are associated with medical procedures. Parental involvement becomes one of the strategies used to improve patient safety. Families who know patient safety can educate themselves to prevent and detect errors that occur during treatment. Education can improve the general knowledge about patient safety. The Speak Up program is recommended by JCAHO to improve effective communication, and this program has a preventive impact on human error. This study aims to determine the effect of education on parent’s ‘speaking up’ knowledge regarding patient safety in the Children's Wards of Dr. Sardjito Hospital in Yogyakarta.Methods: This research study was quasi-experimental using a one group pre-test and post-test design. The intervention in this research was education. The consecutive sampling technique was used with a total of 62 respondents selected. The Speak Up questionnaire and observation sheet to get to know the changes in the knowledge of Speak Up was used to collect the data. The data analysis used a Paired Sample T-Test.Result: The result of the paired T-test showed a p-value <0,001 (p <0,05) which means that there was a significant influence by way of education on parent’s speak up knowledge regarding patient safety.Conclusion: Education improved the parents' speak up knowledge about patient safety.